Evaluation of Live Bacterial Prophylactics to Decrease IncF Plasmid Transfer and Association With Intestinal Small RNAs - Redweik, Graham A. J.; Horak, Mary Kate; Hoven, Ryley; Ott, Logan; Mellata, Melha (Frontiers in Microbiology, 2021)
Chicken intestinal Escherichia coli are a reservoir for virulence and antimicrobial resistance (AMR) genes that are often carried on incompatibility group F (IncF) plasmids. The rapid transfer of these plasmids between bacteria in the gut contributes to the emergence of new multidrug resistant and virulent bacteria that threaten animal agriculture and human health. Thus, the aim of the present study was to determine whether live bacterial prophylactics could inhibit large virulent plasmid transfer and AMR spread in the intestinal tract and the role of smRNA in this process. In this study, we tested ~100 randomly-selected E. coli from pullet feces (n = 3 per group) given no treatment (CON), probiotics (PRO), a live Salmonella vaccine (VAX), or both (P+V). E. coli isolates were evaluated via plasmid profiles and several phenotypic (siderophore production and AMR), and genotypic (PCR for virulence genes and plasmid typing) screens. P+V isolates exhibited markedly-attenuated siderophore production, lack of AMR and virulence genes, which are all related to the loss of IncF and ColV plasmids (P < 0.0001). To identify a causal mechanism, we evaluated smRNA levels in the ceca mucus and found a positive association between smRNA concentrations and plasmid content, with both being significantly reduced in P+V birds compared to other groups (P < 0.01). To test this positive association between IncF plasmid transfer and host smRNA concentration, we evenly pooled smRNA per group and treated E. coli mating pairs with serial concentrations of smRNA in vitro. Higher smRNA concentrations resulted in greater rates of IncF plasmid transfer between E. coli donors (APEC O2 or VAX isolate IA-EC-001) and recipient (HS-4) (all groups; P < 0.05). Finally, RNAHybrid predictive analyses found several chicken miRNAs hybridize with pilus assembly and plasmid transfer genes on the IncF plasmid pAPEC-O2-R. Overall, we demonstrated P+V treatment reduced smRNA levels in the chicken ceca, which was associated with a reduction in potentially-virulent E. coli. Furthermore, we propose a novel mechanism in which intestinal smRNAs signal plasmid exchange between E. coli. Investigations to understand the changes in bacterial gene expression as well as smRNAs responsible for this phenomenon are currently underway.